Precipitation in the Cachoeira River Basin (Northeastern Brazil): trends and variability (1970-2020) - Alves, Jamille Evangelista; Gonçalves, Thiago dos Santos; Nascimento, Sérgio Augusto de Morais (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2022)
This study aims to identify annual and seasonal rainfall trends and variability in the Cachoeira River Basin, State of Bahia (Northeastern Brazil). The data used comprise historical series of total monthly rainfall from six rain stations for 1970-2020 (51 years) obtained from the Hydrological Information System (HidroWeb) of the Agência Nacional de Águas e Saneamento Básico (ANA). The Mann-Kendall, Spearman’s Rho and Sen’s slope tests were satisfactorily applied, allowing the identification of significant trends and magnitudes of precipitation. The analysis showed that statistically non-significant trends prevail in the area. However, a significant negative trend was identified in the central-west region at two rain stations that characterize a reduction of around 300 mm of rain in the studied period. Periods with extreme drought/humidity were recognized and compared with ENSO phases where it was identified that 62.5% of drought events and 42.9% of rainy events can be related to El Niño/La Niña phenomena, respectively. With the coefficient of variation, low rainfall variability was recognized in the eastern portion of the Cachoeira River Basin and high variability in the western part of the area. The results obtained can be used as a reference for the management of water resources in hydrographic basins.